A Descriptive Analysis of School Connectedness: The Views of School Personnel. (January 2016) - Biag, Manuelito
Few studies have investigated school connectedness from the perspectives of the adults working in the school. Using qualitative methods, the present study examined three dimensions of school connectedness in one urban, low-income middle school. Analyses revealed that school personnel cared for students' needs, sometimes at the expense of holding them accountable to rigorous standards. Some respondents assumed that families did not care about their children, and were unable to support them academically or instill in them pro-social values and behaviors. These deficit assumptions influenced how the school disciplined students and engaged with families. Results are discussed with practice and policy implications.